2021
DOI: 10.3390/su132313251
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Ecosystem Services of Shanghai Urban–Suburban Street Trees Based on Low-Carbon Targets

Abstract: Road traffic carbon emissions are an important cause of global warming, and street trees play an important role in regulating road carbon emissions. During urbanization, major differences in the planting management modes and growth status of the street trees in urban–suburban gradient may exist, leading to significant differences in the low-carbon values of the street trees in urban–suburban gradient. Based on this, this study took two typical urban–suburban gradient zones in Shanghai as an example to analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…For the whole tour route, PRA produced the smallest amount of waste gas, whereas 360A produced the largest amount of waste gas. 3 Finding three: the control group algorithms BDA and 360A produced more exhaust gases than PRA, and the different volume values between the control group algorithms and PRA were different in each subsection, reaching the maximum for the whole tour route.…”
Section: Experiments Results Analysis and Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the whole tour route, PRA produced the smallest amount of waste gas, whereas 360A produced the largest amount of waste gas. 3 Finding three: the control group algorithms BDA and 360A produced more exhaust gases than PRA, and the different volume values between the control group algorithms and PRA were different in each subsection, reaching the maximum for the whole tour route.…”
Section: Experiments Results Analysis and Findingsmentioning
confidence: 99%
“…It shows that the collected once-visited scenic spots, regarded as the original data for constructing the recommendation algorithm in this paper, can reflect the different interest tendencies of tourists and ensure that the recommendation algorithm can output the matched scenic spots. 3 Finding three: the functional attribute-weighted value influenced the attribute's capacity for regulating the recommendation result.…”
Section: Experiments Results Analysis and Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that urban street trees are a fragile resource, but the economic value they provide is higher than the management costs. Chen et al [23] investigated the differences in the carbon value of graded street trees along an urban-suburban gradient in Shanghai, China. They found pronounced differences in the carbon reduction contributions between urban and suburban street trees and recommended that special attention be paid to the local degree of urbanization in future construction projects.…”
Section: Introductionmentioning
confidence: 99%
“…At present, research on carbon emissions mainly focuses on quantitative and spatiotemporal analysis of land using information technology such as RS (remote sensing) and GIS (geographical information system) [15][16][17][18][19] . Research on carbon-emitting regions has mainly concentrated on provinces and hot cities [20][21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%